Post-polymerization crosstalk between the actin cytoskeleton and microtubule network. Issue 3 (3rd May 2016) - Joo, E. Emily; Yamada, Kenneth M.
ABSTRACT: Cellular cytoskeletal systems play many pivotal roles in living organisms by controlling cell shape, division, and migration, which ultimately govern morphology, physiology, and functions of animals. Although the cytoskeletal systems are distinct and play different roles, there is growing evidence that these diverse cytoskeletal systems coordinate their functions with each other. This coordination between cytoskeletal systems, often termed cytoskeletal crosstalk, has been identified when the dynamic state of one individual system affects the other system. In this review, we briefly describe some well-established examples of crosstalk between cytoskeletal systems and then introduce a newly discovered form of crosstalk between the actin cytoskeleton and microtubule network that does not appear to directly alter polymerization or depolymerization of either system. The biological impact and possible significance of this post-polymerization crosstalk between actin and microtubules will be discussed in detail.